Bifacial, color-tunable semitransparent perovskite solar cells for building-integrated photovoltaics - Wang, Hao (2020)
Recently, semitransparent perovskite solar cells (ST-PSCs) have received overwhelming attention due to their potential applications in building-integrated photovoltaics (BIPV) and in tandem solar cells. The best ST-PSCs, despite the high efficiency achieved, still show limited bifacial properties and lack esthetic properties. Here, we have demonstrated efficient bifacial colorful ST-PSCs using copper thiocyanate (CuSCN), as a hole-transporting material, in an n–i–p architecture. The n–i–p ST-PSCs exhibit the highest reported bifacial factor of 93.7% and achieve a bifacial equivalent efficiency of 22.1% when illuminated under 1 sun standard conditions on the front side and with a reflected albedo of ∼54.4% from the back side. We have also demonstrated that the colorful appearance of CuSCN-based ST-PSCs can be easily tuned across the entire visible spectrum by tuning either the indium tin oxide (ITO) or the CuSCN thickness without affecting their final efficiency. The wide colorful tunability and excellent bifacial photovoltaic behavior of CuSCN-based ST-PSCs make them a promising candidate for BIPV applications.